Mammalian EGF receptor activation by the rhomboid protease RHBDL2 - Adrain, Colin; Stříšovský, Kvido; Zettl, Markus; Hu, Landian; Lemberg, Marius; Freeman, Matthew (EMBO reports, 2011)
The epidermal growth factor receptor (EGFR) has several functions in mammalian development and disease, particularly cancer. Most EGF ligands are synthesized as membrane-tethered precursors, and their proteolytic release activates signalling. In Drosophila, rhomboid intramembrane proteases catalyse the release of EGF-family ligands; however, in mammals this seems to be primarily achieved by ADAM-family metalloproteases. We report here that EGF is an efficient substrate of the mammalian rhomboid RHBDL2. RHBDL2 cleaves EGF just outside its transmembrane domain, thereby facilitating its secretion and triggering activation of the EGFR. We have identified endogenous RHBDL2 activity in several tumour cell lines.